EFFICACY AND SAFETY OF OLOKIZUMAB IN THE MANAGEMENT OF RHEUMATOID ARTHRITIS- A SYSTEMATIC REVIEW AND META-ANALYSIS - Khalid, Saad; Imran, Laiba; Uzair, Muhammad; Tirmizi, Javeria; Khan, Ayesha; Tashkil, Suman; Adil, Anas (Journal of Ayub Medical College Abbottabad, 2024)
Background: Olokizumab (OKZ) is a monoclonal antibody against the interleukin receptor-6 that has shown promise in recent phase II and III trials in patients of rheumatoid arthritis (RA). This meta-analysis aims to evaluate the efficacy and safety of Olokizumab in managing rheumatoid arthritis. Methods: We searched different databases until March 2023 for randomized controlled trials inspecting the effects of OKZ on various outcomes in RA patients inadequately controlled with anti-TNF or methotrexate. Data were analyzed via Review Manager-v 5.4.1. Relative risks (RR) with 95% confidence intervals were calculated. Results: We evaluated five trials with 2761 patients under four treatment groups: 60mg OKZ administered 2-weekly, 64mg 2-weekly, 64mg 4-weekly, and 120mg 2-weekly. Clinical response as measured by ACR 20, 50, and 70 showed statistically significant improvement with the use of OKZ. A 50% disease improvement was seen across all 4 treatment groups (OKZ 64 mg q2w: RR= 2.96, p<0.0001, OKZ 64mg q4w: RR= 3.06, p=0.0002, OKZ 60 mg q2w: RR=5.06, p=0.007, and OKZ 120mg q2w: RR= 3.63, p=0.04). Moreover, 20% and 70% improvements were also noted with OKZ in doses 64mg 2-weekly and 4-weekly. Disease remission, as indicated by DAS28 <2.6 was also significantly higher than placebo across all groups. Safety data showed comparable mortality rates in treatment and placebo groups (OKZ 64mg q2w: p=0.48, OKZ 64 mg q4w: p=0.93). Conclusion: In conclusion, Olokizumab has shown significant improvement in disease activity compared to placebo with a favourable safety profile. However, further larger and longer-term studies are required to confirm these findings.